(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Wind erodibility of a soil (WE) is a major indicator of itssusceptibility to wind erosion under a given climatic condition. This studyis part of a national project for assessing and mapping wind erodibility ofsoils in Sudan. It was undertaken to generate WE data for the Red SeaState. Three replicate surface soil samples were collected, randomly, fromtwenty-eight geo-referenced farms spread in the State. Non-erodible soilparticles (NEP>0.84mm) and selected soil properties were measuredusing standard procedures. The mean NEP values ranged from 17.0% to57.2% with an overall mean coefficient of variation of replicatedeterminations equal to 4.7%. The equivalent WE ranged from 49.6 to244.0 ton/ha. The results showed a highly significant (P<0.001) increaseof NEP with increase of clay (C) and organic matter (OM), and decreasewith increase of sand and sand plus silt (S+Si) expressed, successively, asratios of clay, clay plus OM and clay plus CaCO3 . The reverse trendswere obtained for the relations of WE and the various soil properties andtheir ratios. Clay, (Si+S)/C, (Si+S)/(C+OM) and (Si+S)/(C+CaCO3 )accounted for 80%, 81%, 81% and 82% of the variation of NEP, and77%, 78%, 78%, and 79% of the variation of WE. Multiple regressionsrelationships of NEP or WE with clay, sand, CaCO 3 and OM gavecoefficients of determinations equal to 81% and 80%, respectively. Thus,it was recommended that clay, (Si+S)/C, (C+OM), (C+CaCO 3 ) ormultiple regression equations may be used for predicting NEP. However,(Si+S)/(C+CaCO3 ) is recommended for predicting NEP, and in all casesthe equivalent WE can be obtained from the standard table. A table forwind erodibility groups was developed for the State.